THE PRACTICE OF BUYING AND SELLING FALSE EYELASHES AND PLANTING SERVICES AMONG STUDENTS OF THE FACULTY OF SHARIA IAIN LHOKSEUMAWE IN THE PERSPECTIVE OF FIQH MUAMALAH - Asra, Siti; Mahdi, Mahdi; Ulfah, Almira Keumala (Corolla International Conference, 2022)
Planting false eyelashes began to be much in demand by female students, they were interested in planting eyelashes because they wanted lentic and beautiful eyelashes without having to take a long time to apply the original eyelashes, and planting false eyelashes will last a long time made from human hair, animal fur and synthesis. This research uses qualitative methods of decluterptal analysis. The practice of buying and selling false eyelashes and their installation services carried out (plastic) and the material is sacred, does not contain feces. The practice of implementing eyelash extension splicing false eyelashes (Eyelash Extension) if eyelashes are worn on the eyelids or on any part of the eye, if it is made of human hair or animal fur then there is no doubt that the law is haram.